A cultura nas margens da educação: formação, ensino e saberes Afroamapaenses na voz de professores de arte - COSTA, Bruno Marcelo de Souza (Universidade Federal do Pará, 2017)
In this research I present discussions about Art Education, Knowledge and Doings Afroamapaenses in Macapá - AP. The work has the theme "Culture on the banks of Education" and as a research subject " knowledge and doings afroamapaenses reinterpreted in the daily lives of teachers of Art and the knowledge and practices of their professional practices . The guiding questions that motivated the research were: a social and cultural groups that these teachers belong and/or self-identify; how they relate to the culture afroamapaense recreated there; that african -Brazilian cultural and artistic practices sharing on your social territory and approaches that exist between culture and curriculum afroamapaense Art worked for these teachers . To better understand the object of study, the research sought dialogue with scholars of history, art and culture and African african - Brazilian, education, curriculum and identity, especially those in the theory of Cultural Studies and Postcolonial Thought based. Thus, thinking about the stories and knowledge that Africans arrived and recreated in Brazil and in the Amazon and how they have been or not worked in teaching Art, decided to investigate these relationships and their consequences through knowledge and practice afroamapaenses practiced by those teachers art of the public schools of the city of Macapa / AP. To achieve the proposed initial goal, used the field of oral history as a methodology, analyzing and interpreting narratives collected from teachers of art, also made use of other resources to capture that information considered relevant, such as: research and educational historical documents ( Plans Education, PPP ) and a questionnaire directed to some of the teachers . The intention was that from the oral narratives of teachers and targeted questionnaires could identify approaches that have the african - Brazilian culture and / or the curriculum afroamapaense "practiced" in the teaching of art and what is the place of stories and knowledge in the lives of African Art teachers. My bet is that heritage and legacies of black diasporic cultures in the Amazon, are latent, live (a) is present in different expressions of the modes of living of teachers of art in the region, especially from Macapá - AP.